Perilaku Pencarian Informasi Tim Pemeriksa Fakta MAFINDO dalam Memverifikasi Kebenaran Informasi di Media Sosial - Ifan Taufiq, Muhammad; Hayati, Nurul (Syarif Hidayatullah State Islamic University of Jakarta, 2023)
Information-seeking behavior is an activity in searching for information that is needed or desired with a specific purpose. This study aims to describe the information-seeking behavior of the Masyarakat Anti Fitnah Indonesia (MAFINDO) fact-checking team. The research method used is a qualitative approach with the type of exploratory research. The data obtained are the results of interviews with MAFINDO fact-checkers as informants and literature studies. The results showed that the information-seeking behavior of the MAFINDO fact-checking team was divided into three stages, namely before searching for information, when searching for information, and after searching for information. Before searching for information, the MAFINDO fact-checking team looked for hoaxes to be verified. When searching for information, the MAFINDO fact-checking team looks for references with predetermined criteria using tools or search engines that match the hoaxes to be verified. After searching for information, the MAFINDO fact-checking team used the references obtained, processed them into fact-checking articles, and published them. The behavior of the MAFINDO fact-checking team in conducting information seeking tends to follow Wilson (1981) information-seeking behavior model, Krikelas (1983) information-seeking behavior model, Wilson (1996) search-behavior model, and Ellis information-seeking behavior model which has been developed and expanded by Meho and Tibbo (2003). And there is no visible tendency to follow Kuhlthau (1991) information-seeking behavior model.